PENGARUH PROSES PEMBUATAN ES KRIM TERHADAP MUTU ES KRIM BERBAHAN BAKU PISANG - Hasanuddin Hasanuddin; Kurnia Herlina Dewi; Insi Fitri (Jurnal Agroindustri, 2011)
Ice cream is a frozen food that could and very favorable in the whole circle and usually consumed as desert. Productions of ice cream by traditional and mid-modern method are methods that have a difference in the production process, especially in the freezing process. The research aimed to understand the influence of production process of ice cream (traditional and mid-modern processes) toward overrun, melt-ability, organoleptic and chemical characteristics. The research used Complete Random Design and factorial by two different factors. The result showed that the highest overrun and the fastest melted of ice cream is K1B2 treatment (banana mid-modern process).